The Relationship Between Understanding Prayer Material and the Practice of Worship at the Bai'turridhwan Tengah Sawah Islamic Boarding School - Ameliana Nurahmi; Novita Safitri; Nurhidayati Nurhidayati (KIPS Institute, 2025)
Islamic Religious Education, especially the subject of fiqh, is a well-established and directed effort to create physically and psychologically obedient human beings who adhere to the rules of worship of a Muslim. Fiqh learning materials have an important role in improving children's worship and elevating their higher status, as well as being happy in life and their lives, therefore religious education must be given to children from an early age. The purpose of this study was to determine the understanding and practice of Fiqh subjects regarding congregational prayer and to determine the relationship between the understanding of fiqh learning materials and the practice of obligatory prayer at the Bai'aturridhwan Islamic boarding school. This study used a quantitative method. Data were collected using questionnaires and product moment tests. After that, the results of the study showed that there was a relationship between the understanding and practice of worship of students at the Bai'aturridhwan Tengah Sawah Islamic boarding school in Bukittinggi. The purpose of this study was to describe the relationship between the understanding and practice of prayer worship of students.